Franchising as a Way of Creating Entrepreneurship and Innovation - Lewandowska, Lucyna (Comparative Economic Research. Central and Eastern Europe, 2014)
The article analyses franchising as a business model based on an economic relationship between the parties. The discussion of the early forms of franchising and of factors stimulating its development in Poland and the world is followed by the presentation of data showing franchise growth trends in Poland for, respectively, domestic and foreign brands. The article highlights the advantages of franchising, which allow it to resist economic crises, stimulate entrepreneurship and innovativeness, and minimise business risks. It also offers a number of comments, observations and conclusions on the synergies that both firms and the Polish economy as a whole can derive from franchising.